2002
DOI: 10.1073/pnas.012027399
|View full text |Cite
|
Sign up to set email alerts
|

Transfer RNA-dependent amino acid biosynthesis: An essential route to asparagine formation

Abstract: Biochemical experiments and genomic sequence analysis showed that Deinococcus radiodurans and Thermus thermophilus do not possess asparagine synthetase (encoded by asnA or asnB), the enzyme forming asparagine from aspartate. Instead these organisms derive asparagine from asparaginyl-tRNA, which is made from aspartate in the tRNA-dependent transamidation pathway [ A sparagine, one of the 21 cotranslationally inserted amino acids that make up proteins, is known to be synthesized from aspartate in an ATP-dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
88
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 90 publications
(93 citation statements)
references
References 40 publications
(36 reference statements)
4
88
0
1
Order By: Relevance
“…Biochemical and genetic studies demonstrated that the tRNA-dependent Asp → Asn conversion is the only route to asparagine biosynthesis available in these organisms. Genome sequence analysis revealed that unless another still unknown enzyme for Asp → Asn conversion exists, Asp/ Glu-AdT is essential for asparagine synthesis in many organisms (Min et al 2002). These data lend support to the notion that the transamidation pathways are intimately linked to amino acid metabolism, as has also been proposed for other aspects of translation (Francklyn 2003; see also below).…”
Section: Translating Glutamine and Asparaginesupporting
confidence: 66%
“…Biochemical and genetic studies demonstrated that the tRNA-dependent Asp → Asn conversion is the only route to asparagine biosynthesis available in these organisms. Genome sequence analysis revealed that unless another still unknown enzyme for Asp → Asn conversion exists, Asp/ Glu-AdT is essential for asparagine synthesis in many organisms (Min et al 2002). These data lend support to the notion that the transamidation pathways are intimately linked to amino acid metabolism, as has also been proposed for other aspects of translation (Francklyn 2003; see also below).…”
Section: Translating Glutamine and Asparaginesupporting
confidence: 66%
“…However, an evolutionary change from D-AspRS to ND-AspRS may have also been logical, if one considers that Asp-tRNA Asn may not be as toxic to cellular protein synthesis as had been expected (B. Min, personal communication). The presence of a ND-AspRS may be beneficial in other ways, for instance, in case an organism needs to make asparagine (13). Therefore, it may be advantageous for an organism to retain ''flexibility'' with tRNA discrimination conversions in either direction, possibly in response to codon-usage drift or changing metabolic environments.…”
Section: Discussionmentioning
confidence: 99%
“…The archaeal genre comprises all archaeal AspRS enzymes, as well as one of two types of AspRSs found in the bacteria Thermus thermophilus (12), Deinococcus radiodurans (13), and Clostridium acetobutylicum. Whereas the archaeal AspRS enzymes were thought to be nondiscriminating (12,14), it is now known that in several archaea (including Thermococcus kodakaraensis), this enzyme is discriminating (15).…”
mentioning
confidence: 99%
“…(Planctomycetales). Among these species, it has been shown that the genome of D. radiodurans does not encode the regular enzymes for asparagine biosynthesis (asnA or asnB) and that Asp-tRNA Asn transamidation is the only pathway by which D. radiodurans can synthesize asparagine (28). The coexistence of GatCAB with AsnRS and GlnRS might then be explained in the nine organisms where GatCAB coexists with AsnRS and GlnRS by a role of GatBCA in the biosynthesis of asparagine or glutamine.…”
mentioning
confidence: 99%